INVESTIGATION: LEARNING TAHFIDZ QUR'AN FOR STUDENTS WITH SPECIAL NEEDS IN ISLAMIC-BASED SCHOOLS - Muchamad Irvan; Ahsan Romadlon Junaidi; Atifah Nur Zahidah; Nurul Fitra Febriana; Siti Mutmainah (Universitas Negeri Malang, 2023)
Discussions regarding the ability of children with special needs to follow tahfidz of the Qur'an often arise,